The Effect of the Persuasive Guide Strategy on the Cognitive Representation of Information in the Curriculum and Textbook Subject for Students of the Departments of Educational and Psychological Sciences - dr. Zahraa Ali Karim (Journal of College of Education, 2025)
This research aims to examine the effect of the persuasive guide strategy on the cognitive representation of information in the curriculum and textbook subject for students of the departments of educational and psychological sciences. To achieve this, the researcher formulated the null hypothesis, which states that there is no statistically significant difference at the 0.05 significance level between the mean scores of the experimental group students who study the curriculum and textbook subject according to the persuasive guide strategy and the mean scores of the control group students who study the same subject according to the traditional method on the cognitive representation of information scale. The sample size consisted of 88 students, with 43 students in the experimental group and 45 students in the control group for the academic year (2024-2025) of the second course. The researcher adopted the cognitive representation of information scale by Al-Quraishi (2023), which consists of 68 items, and its validity and reliability were verified. The scale was then applied to the research sample. After analgising the data statistically, the results showed a statistically significant difference in the cognitive representation of information scale in favour of the experimental group.
Keywords: Persuasive Guide Strategy, Cognitive Representation of Information